TDP-43 interacts with mitochondrial proteins critical for mitophagy and mitochondrial dynamics. (21st June 2018) - Davis, Stephani A.; Itaman, Sheed; Khalid-Janney, Christopher M.; Sherard, Justin A.; Dowell, James A.; Cairns, Nigel J.; Gitcho, Michael A.
Highlights: TDP-43 is a major pathological protein in neurodegenerative diseases and interacts with several mitochondrial proteins. TDP-43 interacts with and regulates MFN2 and PHB2 affecting mitochondrial dynamics and mitophagy. We discovered N-terminal 27 kDa and C-terminal 30 kDa TDP-43 fragments in mitochondrial fractions. Overexpression of the mitochondrial processing peptidase alpha subunit, PMPCA, increased 27 kDa N-terminal TDP-43 expression. These observations may provide novel insights into the role TDP-43 plays in mitochondrial dysfunction. Abstract: Transactive response DNA-binding protein of 43 kDa (TDP-43) functions as a heterogeneous nuclear ribonucleoprotein and is the major pathological protein in frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis/motor neuron disease (ALS/MND). TDP-43 pathology may also be present as a comorbidity in approximately 20–50% of sporadic Alzheimer's disease cases. In a mouse model of MND, full-length TDP-43 increases association with the mitochondria and blocking the TDP-43/mitochondria interaction ameliorates motor dysfunction. Utilizing a proteomics screen, several mitochondrial TDP-43-interacting partners were identified, including voltage-gated anion channel 1 (VDAC1) and prohibitin 2 (PHB2), a crucial mitophagy receptor. Overexpression of TDP-43 led to an increase in PHB2 whereas TDP-43 knockdown reduced PHB2 expression in cells treated with carbonyl cyanide m-chlorophenylhydrazone (CCCP), an inducer of mitophagy. These results suggest that TDP-43 expression contributes to metabolism and mitochondrial function however we show no change in bioenergetics when TDP-43 is overexpressed and knocked down in HEK293T cells. Furthermore, the fusion protein mitofusin 2 (MFN2) interacts in complex with TDP-43 and selective expression of human TDP-43 in the hippocampus and cortex induced an age-dependent change in Mfn2 expression. Mitochondria morphology is altered in 9-month-old mice selectively expressing TDP-43 in an APP/PS1 background compared with APP/PS1 littermates. We further confirmed TDP-43 localization to the mitochondria using immunogold labeled TDP-43 transmission electron microscopy (TEM) and mitochondrial isolation methods There was no increase in full-length TDP-43 localized to the mitochondria in APP/PS1 mice compared to wild-type (littermates); however, using C- and N-terminal-specific TDP-43 antibodies, the N-terminal (27 kDa, N27) and C-terminal (30 kDa, C30) fragments of TDP-43 are greatly enriched in mitochondrial fractions. In addition, when the mitochondrial peptidase (PMPCA) is overexpressed there is an increase in the N-terminal fragment (N27). These results suggest that TDP-43 processing may contribute to metabolism and mitochondrial function.